Influence of toe-hang vs. face-balanced putter design on golfer applied kinetics - MacKenzie, S.; Henrikson, E. (Proceedings, 2018)
The influence of the location of the center of mass (cm) of the putter head, relative to the shaft, on golfer applied kinetics at the grip was investigated. Participants made 12 attempts at a straight up-hill (2.2° slope) 8 ft putt with half of the attempts executed using a PING Anser 4 toe-hang putter (TH) and half with an Anser 5 face-balanced putter (FB). The net torque applied by the golfer, acting about the long axis of the shaft, was significantly greater in magnitude with the TH putter in comparison to the FB putter. The TH putter was also associated with a higher angular velocity about the shaft and a more open face at impact. These findings may have important implications for fitting the style of putter to a particular stroke or individual golfer as golfer applied kinetics would be strongly associated with the `feel` of a putter.